(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
In this study, the possibility of using kiwi peels as natural adsorbents for reducing nitrate concentration in water was considered. Various periods of time (30, 60, 90,120,150,180) minutes were done to detect the best contact time with initial nitrate concentration Co=50ppm, amount of adsorbent =1.0 gm. The results revealed that the equilibrium state of adsorption is approached after a contact time of 180 min and removal efficiency (R%=37.78). The effect of amount of adsorbent on nitrate adsorption, was studied by adding various amounts of adsorbent, (1, 1.5, 2, 2.5,3 gm.) with initial nitrate concentration (50 mg/l) and contact time of (3 hours). The results revealed that there was a relationship between the increase in the adsorbent amount (gram) and the increase in removal efficiency and that is due to the increase in the surface area available for adsorption process. Three initial concentrations of nitrate solution were examined (50, 75 and 100 mg/l) with amount of adsorbent of (1.0 gm.) and contact time of (3 hours). It is noticed that the adsorption rate increases with increasing the initial concentration. Also it is found that the best removal efficiency of nitrate occurs at initial concentrations of 100 mg/l.